Komunikasi Digital Pada Organisasi Masjid Sebagai Pengembangan Daerah - Jeratallah Aram Dani; Bayu Mukti (Jurnal Syntax Transformation, 2023)
Digital communication is very necessary for today's organizations, which support even the needs that need to be carefully prepared. Digital here is not all robot automation, but is operated by humans to optimize media systems that are adjusted to segmentation. Organizations in mosques are also needed to provide information about Islam and guidelines that apply to Muslims, as well as provide knowledge and enrichment in daily activities in mosques to worship and increase faith in Allah SWT and Prophet Muhammad SAW. Mosques are one of the parameters in the development of certain cities or areas, where the productivity of prospering mosques will have a positive impact and benefit the community, especially Muslims. The research method carried out uses a qualitative approach, by conducting observations and direct interviews with several mosque takmirs. The result of this study is to provide information about the truth of mosque buildings and their management making the area iconic for migrants to come to certain areas because they want to worship and visit the mosque